Synthesis of Wasathiyah and Deep Ecology to Build a Post-Anthroposcentric Environmental Ethics - Muchammad Ulin Nuha (UIN Maulana Malik Ibrahim Malang, 2026)
The looming global ecological crisis shows that environmental damage is not only material, but rooted in a paradigm crisis that places humans at the center of life. The dominance of the anthropocentric perspective has been proven to give birth to massive resource exploitation and ecosystem degradation. Various technocratic approaches and scientific policies have not been able to answer the root of this problem, so a more comprehensive paradigm of environmental ethics is needed that involves spiritual and moral dimensions. This research offers an Ecospiritual Moderation model, which is a conceptual synthesis between Wasathiyah values in Islamic ethics and the principles of Deep Ecology as a radical critique of anthropocentrism. Through the conceptual inquiry method based on textual analysis and literature comparison, this study examines the relevance of Wasathiyah such as tawazun, adl, amanah, and the prohibition of israf in strengthening the ethics of cosmic balance, as well as connecting it with the idea of Deep Ecology about the intrinsic value of nature, biosphere equality, and ecological self. The results of the study show that the integration of the two perspectives results in a post-apocentric environmental ethical framework that is not only rational philosophical, but also spiritual-transformative. The Ecospiritual Moderation Model has practical implications for the development of environmental education, public policy, and social movements based on moderate spirituality. Thus, this research makes a theoretical contribution in expanding the global environmental ethics discourse and presenting a new paradigm that is more just, sustainable, and rooted in human values and Islamic spirituality. Krisis ekologis global yang kian mengancam menunjukkan bahwa kerusakan lingkungan tidak hanya bersifat material, tetapi berakar pada krisis paradigma yang menempatkan manusia sebagai pusat kehidupan. Dominasi cara pandang antroposentris terbukti melahirkan eksploitasi sumber daya dan degradasi ekosistem yang masif. Berbagai pendekatan teknokratis dan kebijakan ilmiah belum mampu menjawab akar persoalan ini, sehingga diperlukan paradigma etika lingkungan yang lebih komprehensif dan melibatkan dimensi spiritual serta moral. Penelitian ini menawarkan model Moderasi Ekospiritual, yaitu sintesis konseptual antara nilai-nilai Wasathiyah dalam etika Islam dan prinsip Deep Ecology sebagai kritik radikal terhadap antroposentrisme. Melalui metode conceptual inquiry berbasis analisis tekstual dan perbandingan literatur, penelitian ini menelaah relevansi Wasathiyah seperti tawazun, adl, amanah, dan larangan israf dalam memperkuat etika keseimbangan kosmik, sekaligus menghubungkannya dengan gagasan Deep Ecology tentang nilai intrinsik alam, kesetaraan biosferis, dan ecological self. Hasil penelitian menunjukkan bahwa integrasi kedua perspektif menghasilkan kerangka etika lingkungan pascantroposentris yang tidak hanya rasional filosofis, tetapi juga spiritual-transformatif. Model Moderasi Ekospiritual memiliki implikasi praktis bagi pengembangan pendidikan lingkungan, kebijakan publik, dan gerakan sosial berbasis spiritualitas moderat. Dengan demikian, penelitian ini memberikan kontribusi teoretis dalam memperluas wacana etika lingkungan global dan menghadirkan paradigma baru yang lebih berkeadilan, berkelanjutan, dan berakar pada nilai-nilai kemanusiaan serta spiritualitas Islam.